tsxwi’xwi’em’: Four new Hul’q’umi’num’ stories - Louie, Carol (2019)
I present four original stories in my First Nations language, Hul’q’umi’num’, a Salish language spoken in southwestern British Columbia, Canada. To assist in the understanding of the stories, I have provided a glossary and interlinear analysis for each. These are true stories relating my experiences growing up in a Coast Salish family in the territory of the Quw’utsun’ people. The first and second stories are about childhood frights and surprises. The third and fourth stories are about mistakes that I made and what I learned from them. By passing these stories on to the next generation, I hope to have opened a doorway to the language for teachers and learners.